Group antenatal care (Pregnancy Circles) for diverse and disadvantaged women: study protocol for a randomised controlled trial with integral process and economic evaluations - Meg Wiggins; Mary Sawtell; Octavia Wiseman; Christine McCourt; Sandra Eldridge; Rachael Hunter; Ekaterina Bordea; Connor Mustard; Ainul Hanafiah; Bethan Hatherall; Vivian Holmes; Anita Mehay; et al. (BMC, 2020)
Abstract Background Group antenatal care has been successfully implemented around the world with suggestions of improved outcomes, including for disadvantaged groups, but it has not been formally tested in the UK in the context of the NHS. To address this the REACH Pregnancy Circles intervention was developed and a randomised controlled trial (RCT), based on a pilot study, is in progress. Methods The RCT is a pragmatic, two-arm, individually randomised, parallel group RCT designed to test clinical and cost-effectiveness of REACH Pregnancy Circles compared with standard care. Recruitment will be through NHS services. The sample size is 1732 (866 randomised to the intervention and 866 to standard care). The primary outcome measure is a 'healthy baby' composite measured at 1 month postnatal using routine maternity data. Secondary outcome measures will be assessed using participant questionnaires completed at recruitment (baseline), 35 weeks gestation (follow-up 1) and 3 months postnatal (follow-up 2). An integrated process evaluation, to include exploration of fidelity, will be conducted using mixed methods. Analyses will be on an intention to treat as allocated basis. The primary analysis will compare the number of babies born "healthy" in the control and intervention arms and provide an odds ratio. A cost-effectiveness analysis will compare the incremental cost per Quality Adjusted Life Years and per additional 'healthy and positive birth' of the intervention with standard care. Qualitative data will be analysed thematically. Discussion This multi-site randomised trial in England is planned to be the largest trial of group antenatal care in the world to date; as well as the first rigorous test within the NHS of this maternity service change. It has a recruitment focus on ethnically, culturally and linguistically diverse and disadvantaged participants, including non-English speakers. Trial registration Trial registration; ISRCTN, ISRCTN91977441 . Registered 11 February 2019 - retrospectively registered. The current protocol is Version 4; 28/01/2020.